Application of Wireless Power Transfer to Railway Parking Functionality: Preliminary Design Considerations with Series-Series and LCC Topologies. (27th December 2018) - Pugi, Luca; Reatti, Alberto; Corti, Fabio
Abstract : There is a wide literature concerning the application of inductive power transfer (IPT) to light railway systems. In this work, proposed application is innovative with respect to existing literature: static current collection on conventional railway lines is proposed in order to replace the functionalities implemented by conventional battery chargers and the so-called railway "parking" system. According to standards in force, current collection in standstill conditions is limited since pantograph contact shoes and catenary wires have to be protected by thermal overload. These limitations have to be considered since power demand for all the services installed on modern coaches should be higher than 20-40kW. This is a critical technical issue especially for long compositions that have to be prepared for service by activating on-board subsystems such as heating and air conditioning. Additional possible applications should be related to refrigerated wagons in freight compositions. In all these cases the availability of a simple, safe, and compact system should be useful to ensure a wireless power collection to on-board equipment. In this work authors introduce the proposed application and perform some preliminary design considerations. With respect to current literature on IPT systems, authors also introduce some innovative design criteria based on the analogy between resonant electrical system and corresponding mechanical ones. In this way, sizing of the proposed IPT system can be performed using modal methods that are also used for the proper sizing of mechanical vibrating systems, such as example, vehicle suspensions, or pantograph systems.